Mechanisms of virus dissemination in bone marrow of HIV-1infected humanized BLT mice - Mark S Ladinsky; Wannisa Khamaikawin; Yujin Jung; Samantha Lin; Jennifer Lam; Dong Sung An; Pamela J Bjorkman; Collin Kieffer (My University, 2019)
Immune progenitor cells differentiate in bone marrow (BM) and then migrate to tissues. HIV-1 infects multiple BM cell types, but virus dissemination within BM has been poorly understood. We used light microscopy and electron tomography to elucidate mechanisms of HIV-1 dissemination within BM of HIV-1-infected BM/liver/thymus (BLT) mice. Tissue clearing combined with confocal and light sheet fluorescence microscopy revealed distinct populations of HIV-1 p24-producing cells in BM early after infection, and quantification of these populations identified macrophages as the principal subset of virus-producing cells in BM over time. Electron tomography demonstrated three modes of HIV-1 dissemination in BM: (i) semi-synchronous budding from T-cell and macrophage membranes, (ii) mature virus association with virus-producing T-cell uropods contacting putative target cells, and (iii) macrophages engulfing HIV-1-producing T-cells and producing virus within enclosed intracellular compartments that fused to invaginations with access to the extracellular space. These results illustrate mechanisms by which the specialized environment of the BM can promote virus spread locally and to distant lymphoid tissues.
Keywords: Humanized mouse; Virus-based gene therapy research